Executive functions: Exploration of the “Behavior Rating Inventory of Executive Function” (BRIEF) in 6-12 aged children - Τάνταρος Σπύρος; Νικολάου Όλγα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Abstract is available in the PDF